The Influence of Institutional Investors on Myopic R&D Investment Behavior - Bushee, Brian J. (The Accounting Review, 1998)
[This paper examines whether institutional investors create or reduce incentives for corporate managers to reduce investment in research and development (R&D) to meet short-term earnings goals. Many critics argue that the frequent trading and short-term focus of institutional investors encourages managers to engage in such myopic investment behavior. Others argue that the large stockholdings and sophistication of institutions allow managers to focus on long-term value rather than on short-term earnings. I examine these competing views by testing whether institutional ownership affects R&D spending for firms that could reverse a decline in earnings with a reduction in R&D. The results indicate that managers are less likely to cut R&D to reverse an earnings decline when institutional ownership is high, implying that institutions are sophisticated investors who typically serve a monitoring role in reducing pressures for myopic behavior. However, I find that a large proportion of ownership by institutions that have high portfolio turnover and engage in momentum trading significantly increases the probability that managers reduce R&D to reverse an earnings decline. These results indicate that high turnover and momentum trading by institutional investors encourages myopic investment behavior when such institutional investors have extremely high levels of ownership in a firm; otherwise, institutional ownership serves to reduce pressures on managers for myopic investment behavior.]